2017
DOI: 10.4269/ajtmh.16-1028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Risk Proximity in the Beliefs and Behaviors Related to Mosquito-Borne Diseases: The Case of Chikungunya in French Guiana

Abstract: Abstract.Human behaviors are increasingly recognized to play a key role in the spread of infectious diseases. Although a set of social and cognitive determinants has been consistently found to affect the adoption of health protective behaviors aiming to control and prevent a variety of infections, little is currently known about the ecological drivers of these behaviors in epidemic settings. In this article, we took advantage of the outbreak of chikungunya, a reemerging mosquito-borne disease, that occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Besides cognitive determinants, attitudes of individuals play a great role in the adoption of protective behaviors for the prevention and control of infectious diseases. 32 A good or favorable attitude toward disease prevention and control among the younger generation, especially university students, is highly desired to apply good preventive practice during their campus stay in endemic areas. Moreover, the younger generation can spread the important information to a wider community.…”
Section: Discussionmentioning
confidence: 99%
“…Besides cognitive determinants, attitudes of individuals play a great role in the adoption of protective behaviors for the prevention and control of infectious diseases. 32 A good or favorable attitude toward disease prevention and control among the younger generation, especially university students, is highly desired to apply good preventive practice during their campus stay in endemic areas. Moreover, the younger generation can spread the important information to a wider community.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in mind that these contexts are different from Guyana, the results of such studiesamong others (i.e. mixed method and qualitative studies)-are inconclusive regarding the association between knowledge and behavior: some find a positive association [10][11][12][13][14][15], whereas other find a negative [16] or no association [17][18][19][20][21][22]. This diversity in the findings suggests that the results are context specific and cannot be generalized across different areas/regions and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the ACEs group, participants with higher household risk showed more target behaviours in relation to the elimination of mosquito breeding sites. In the literature, some studies have shown that the perception of those residing in risk areas is different from those in areas with lower risk [31], and there are differences between those who live in urban and rural areas [28]. The ndings of the present work give rise to some working hypotheses, which can be tested in further studies with larger samples.…”
Section: Discussionmentioning
confidence: 58%